PENGARUH REKRUTMEN DAN SELEKSI KARYAWAN TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT. Pegadaian (Persero) Kanwil II - Pekanbaru) - Riko Randika; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to analyze employee recruitment and employee selection and its effect on employee performance at PT. Pegadaian Kanwil II Pekanbaru. Employee recruitment as a variable (X1), employee selection as a variable (X2), and Employee Performance as a variable (Y). The method used in this study is descriptive and quantitative using the SPSS 21 program, where the sample used is 87 employees conducted by simple random sampling and data collection techniques through questionnaires. The results of the analysis use the validity test, reliability test, determination test, simple linear regression test, multiple linear regression test, t test and F test. So that it can be concluded that employee recruitment has a significant effect on the performance of employees of PT. Pegadaian Kanwil II Pekanbaru, employee selection has a significant effect on employee performance at PT. Pegadaian Kanwil II Pekanbaru, and employee recruitment and employee selection have a significant effect on the performance of PT. Pegadaian Kanwil II Pekanbaru. Keywords: Employee Recruitment, Employee Selection and Employee Performance